Student Teachers Perception towards the Self-Blend Model of the Blended Learning Approach - Arokia Marie, Maria Josephine; Nagaraju, M.T.V (Indian Journal of Educational Technology, 2024)
Recognizing the Self-Blend Model (SBM), this paper is an attempt to report improved student teachers’ perception through implementing the Blended Learning Approach (BLA). ODM allows students to work at far-flung places and materials are primarily delivered through the online platform with the assistance of teachers. Students are allowed to interact with teachers in the regular classroom and on online platforms too if they have doubts. The online learning management EDMODO (ED-LMS) was used and the intervention lasted for eight weeks. 54 student teachers were used as samples for the study and the methodology used was the experimental method (Awad Soliman Keshta, Ismail Ibrahim Harb 2013). A quantitative analysis non-parametric test was used to analyze the student teachers’ perception towards SBM by Blended Learning Approach (BLA). The perception scale was comprised of the following dimensions Gen (general), II (Improved interactivity), KD (knowledge design), MU (Material Used), TA (technology assistance), and PS (predominant satisfaction). The student teachers showed approving perception in the direction of the use of BLA for the SBM. The experimental group students of College XXX1 of Education showed higher positive performance than the control group students of College XXX2 of Education from Pondicherry, India. The result of the study shows that student teachers developed a positive perception of BLA. Hence the study recommends that stakeholders implement BLA in the teaching and learning process.